Fixing hell an army psychologist confronts Abu Ghraib - James, Larry C. (Grand Central Publishing, 2008)
This is the story of Abu Ghraib that you haven't heard, told by the soldier sent by the Army to restore order and ensure that the abuses that took place there never happen again.